Analytical current Model for Dual Material Double Gate Junctionless Transistor - santosh chandrakant wagaj; shailaja chandrakant patil (IAES Indonesian Section, 2019)
A Transistor model with bulk current is proposed in this article for long channel dual material double gate junction less transistor. The influence of different device parameters such as body thickness, channel length, oxide thickness, and the doping density on bulk current is investigated. The proposed model is validated and compared with simulated data using Cogenda TCAD. The model is designed by Poison’s equation and depletion approximation. Current driving capability of MOSFET is improved by dual material gate compare to single material gate.